Intelektualna in konceptualna struktura področja urbanega gozdarstva v Sloveniji in svetu - Nastran, Mojca (Acta silvae et ligni, 2025)
The article provides an overview of published articles and topics covered in the international scientific journal Urban Forestry and Urban Greening (UFUG) and students' final theses up to 2023. The analysis includes 2,550 scientific articles published in UFUG between 2002 and 2023, as well as 88 final theses published in Slovenia. To compare developments, we divided this material into four comparative periods, extracted the authors' keywords from the articles, and assigned each one to a single subcategory. We then analysed the terms used in the titles and abstracts of UFUG articles. In addition to the increase in the number of articles published, the number of articles using keywords related to biodiversity and nature conservation has also increased over the past two decades. The results show that interest among authors has declined the most in field of politics and management, while an interdisciplinary expansion has been observed mainly in the fields of health and psychology. We estimate that interdisciplinary expansion will continue in the future and ultimately transition into transdisciplinarity.
Keywords: bibliometric analysis; bibliometrična analiza; keywords; mestni gozdovi; predmetne oznake; urban forestry; Urban Forestry and Urban Greening; urban forests; urbano gozdarstvo; VOSviewer